KONTRUKSI BERITA KEBUDAYAAN HUMAS KOTA PALEMBANG PADA WEBSTITE: bakohumas.palembang.go.id - eka yati, Sri; Budi Santoso; Arif Ardiansyah; Hamzah (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
Local culture is an important element in a society. Local culture must be maintained and protected, just like the local culture in Palembang City. Songket weaving culture is one of the most valuable regional cultural assets in Palembang City. Songket weaving itself is a tradition carried out by the people of Palembang. One of the activities carried out by the Palembang City government through Palembang City Public Relations is to make news about the local culture of Palembang City (Songket Weaving). The news was published on online media or the Palembang City Public Relations website www.bakohumas.palembang.go.id. Based on the results of the study, it was found that the local culture of Palembang City, namely songket woven fabric, was published in online media or the Palembang City Public Relations website www.bakohumas.palembang.go.id. With the title "Palembang Songket Motif Proposed to Become a Cultural Heritage" On Friday, May 19 2023, news construction on headlines or news titles. Headlines based on news interests, from the results of the study it was found that the banner headline type. Furthermore, based on the compatibility of the line (deck) of the Flush left headline type. Based on news placement, news includes Top headlines. The next news construction is the lead or news terrace. Lead is based on the emphasis on the 5W + 1H element, namely what leads. Furthermore, leads based on stylistics (style of language), in the news are of the digest lead type. Then, leads based on the type of words or sentences are not found in the news. Based on the Body (Completeness or News Explanation) of Block Paragraph type.